Porous structure of carbon materials obtained from the shell of walnuts - Ivanichok, N.Ya.; Ivanichok, O.M.; Kolkovskyi, P.I.; Rachiy, B.I.; Sklepova, S.-V.S.; Kulyk, Yu.O.; Bachuk, V.V. (Physics and Chemistry of Solid State, 2022)
Samples of porous carbon material (PCM) were obtained by carbonization of the feedstock (walnut shells). Small-angle X-ray scattering (SAXS) was used to study the porous structure of the obtained carbon materials. The fractal dimension of the surface increases and significant changes are observed in the distribution of the pore volume of the PCM samples with an increase in the carbonization temperature of the initial feedstock, which is especially pronounced for the sample obtained at 700 °C. It is shown that PCM obtained at 400-700 °С are macroporous materials, the maximum porous volume corresponds to pores with radius R ≈ 30 nm, and samples obtained at 700-1000 °C are mesoporous with R ≈ 5 nm. The characteristics of the porous structure of the obtained materials were calculated on the basis of isotherms of low-temperature adsorption-desorption of nitrogen and it was shown that the carbonization temperature significantly affects the specific surface area and pore volume of PCM. It was determined that to obtain of PCM with an optimal ratio of micro- and mesopores, the temperature is 800 °C, at which the specific surface area of the carbon material is 238 m2/g with an average pore diameter of 2.2 nm.